Engrailed-1 Negatively Regulates β-Catenin Transcriptional Activity by Destabilizing β-Catenin via a Glycogen Synthase Kinase-3β–independent Pathway - Bachar-Dahan, Liora (The American Society for Cell Biology, 2006)
The Wnt signaling pathway plays a major role in development, and upon deregulation it is implicated in neoplasia. The hallmark of the canonical Wnt signal is the protection of β-catenin from ubiquitination and proteasomal degradation induced by glycogen synthase kinase (GSK)-3β inhibition. The stabilized β-catenin translocates to the nucleus where it binds to T-cell factor/lymphoid enhancer factor (TCF/LEF) transcription factors, activating the expression of Wnt target genes. In the absence of Wnt signal, TCF/LEF bind to Groucho (Gro)/TLE corepressors and repress Wnt target genes. Gro/TLE bind also to Engrailed (En) transcription factors mediating En-repressive activity on En target genes. Here, we present data suggesting that En-1 serves also as a negative regulator of β-catenin transcriptional activity; however, its repressive effect is independent of Gro/TLE. Our data suggest that En-1 acts by destabilizing β-catenin via a proteasomal degradation pathway that is GSK-3β–independent. Moreover, because En-1-mediated β-catenin degradation is also Siah independent, our data imply that En-1 exerts its repressive effect by a novel mechanism negatively controlling the level of β-catenin.